Üsküdar Yeni Camii ve Külliyesi - Akbulut, Müşfika (My University, 2003)
IV. Mehmed'in eşi, II. Mustafa ve III. Ahmed'in annesi Gülnûş Emetullah Valide Sultan tarafından, Kayseri'li mimar Mehmet Ağa'ya 1120-1122 (1710-1712) yılları arasında inşa ettirilen Yeni Valide Külliyesi, camii, sebil, iki çeşme, sıbyan mektebi, muvakkithâne, türbe, hazîre, dükkânlar ve imâretten meydana gelmektedir. Üsküdar İskele meydanında bulunan külliye, güneydoğuda Hakimiyet-i Milliye caddesi, kuzeydoğuda Balaban caddesi, batıda İmam Nasır sokağı ile sınırlandırılmış dikdörtgene yakın bir alanda kurulmuştur. Külliyenin merkezini, büyük bir dış avlu tarafından kuşatılan ve merkezi kubbeli planın uygulandığı cami oluşturur. Caminin güneydoğu tarafına, sebil, türbe, muvakkithâne ve hazîre, kuzeydoğusuna dükkânlar, kuzey giriş kapısı üzerine sıbyan mektebi, doğu ve batısına da birer çeşme yerleştirilmiştir. Külliyeden bağımsız olarak inşa edilmiş olan imâret ise, caminin kuzeyinde bulunmaktadır. Yapı topluluğunu kuşatan dış avlu duvarının sınırları içinde kalan bölümde de, avlunun batısında, Bedesten kapısı karşısında su deposu, kuzeyinde yangın havuzu, helâlar ve abdest muslukları bulunmaktadır. Klasik dönem külliye ögelerinde olduğu gibi, yerleşmelerinde ve birbirleriyle olan ilişkilerinde simetrik ve geometrik düzen gösteren Yeni Camii ve Külliyesi yapılarında, Lale Devri diye isimlendirilen, Osmanlı sanatında Batı etkilerinin görülmeye başladığı bir dönemde inşa edilmiş olmaları sebebiyle dönemin karakteristlik özellikleri de gözlenmektedir. Hünkâr kapısı girişinde sağda yer alan çeşme bu özelliklerin en fazla kullanıldığı yapıdır. Dört bölümden oluşan çalışmamızın amacı, Osmanlı İmparatorluğu'nda Batı etkilerinin görülmeye başladığı bir dönemde inşa edilen, Osmanlı klasik mimarisinin son temsilcisi olan Üsküdar Yeni Camii ve Külliyesi'nin, mimarisi ve süslemesi ile Osmanlı sanatı içindeki yerinin incelenerek değerlendirilmesidir. Yeni Camii and its Külliyah (whole considerable construction) was built by the order of Gülnuş Emetullah Valide Sultan, the mother of the Sultan IInd Mustafa and IIIrd Ahmed and Spouse of IVth Mehmed by the architect Mehmet Tahir Ağa from Kayseri between the years of 1120 - 1122 (1710 -1712) and it came into existence from mosque, public fountain, two fountains, school for children, muvakkithâne, tomb, place for the graveyard, shops and charitable establishment The külliyah (the whole considerable construction) is built at the Square of Üsküdar Landing-place and surrounded with Hakimiyet-i Milliye caddesi (street) in the southeast , Balaban caddesi (street) in the northeast , İmam Nasır sokağı (street) in the west, on the area like a rectangle. The center of the Külliyah (the whole considerable construction) came into existence with a big out garden surrounded and the mosque which is built by being performed a plan of big dome. A public fountain, a tomb, muvakkithâne, place for the grave yard is placed to the southeast of the mosque ; the shops are built to the northeast ; the school for children is built to the north entrance gate and each gates are placed to the east and west ; and the public improvement which is build free from the külliyah (the whole considerable construction) takes place at the north side of the mosque. There are water tank at the opposite of the Bedesten gate in the west of the courtyard , fire-pool toilets and ablusion place at the north , in the out walls of the construction which surround the whole buildings. Just like in the classic period külliyah (the whole considerable construction), the characteric affects of the west architecture in the Ottoman arts can be seen in the building art of Lale Devri (Tulip Period) at the relationship in the buildıngs of the külliyah (the whole considerable constructions) which were built in geometric and simetric organisation. The foundation which takes place on the right at the entrance of Sultan gate , is the constraction where these spezifications are used mostly. The aim of our work which consists of four parts , is to inspect and value the Mosque of Üsküdar Yeni Camii and its ( whole considerable construction) that is carrying on the affection of the West architecture which was seen sharply on the Ottoman Classic Arhitecture as the last represantatıve sample for the westliche affect on the Ottoman architecture; and thus to examine the architectural structure of Üsküdar Yeni Camii and its ( whole considerable construction) with its architectural and adorning art in Ottomans art .
Keywords: Camiler _ Türkiye_ İstanbul; Camiler ve minareler; Dini ve benzeri amaçlı yapılar; Güzel ve dekoratif sanatlar; Mimarlık